A Novel de novo Translocation (derXt(X;13) (q25;q12.11)dn) Manifesting As A Phenotypic Overlap with A Glycosylation Disorder: A Case Report - Hart, Caroline; Crushell, Ellen; Curran, Padraic; Brenner, Clare; Lynch, Bryan; Lefeber, Dirk J.; Lynch, Sally Ann; Fitzsimons, Patricia; Knerr, Ina (Archives of Clinical and Medical Case Reports, 2025)
We describe a novel de novo translocation (derXt(X;13)(q25;q12.11)dn) manifesting as a phenotypic overlap with a Congenital Disorder of Glycosylation (CDG) in a 7-year-old girl. We characterize the clinical, biochemical and neuro-radiological phenotype of this unique and hitherto undescribed translocation, and discuss etiologic aspects in the context of a phenotypic overlap with a CDG.